Iceland’s Financial Crisis in 2008. Political, Economic and Social Consequences - Legutko, Agnieszka Joanna (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
The author analyzes the successful strategy of overcoming financial breakdown in the case study of Iceland. The aim of the article is to verify a hypothesis that the Icelandic model could become a panacea for future crises? A document analysis method is applied to present essential indicators such as GDP and trade balance. With the use of a source analysis method, the collapse of the financial sector is determined as the main cause of the slump. The systematization of crisis events is introduced and deepened by the social and political situation. Changes in the state’s condition after the crash are provided and future forecasts about economic development are discussed. As a summing up, the author disapproves of the hypothesis that the Icelandic model of overcoming the financial breakdown as a panacea for future crises, pointing out that it is only applicable for specific cases and cannot be seen as a magical remedy for every kind of crisis.